Labour induction near term for women aged 35 or over: an economic evaluation. (16th March 2017) - Walker, KF; Dritsaki, M; Bugg, G; Macpherson, M; McCormick, C; Grace, N; Wildsmith, C; Bradshaw, L; Smith, GCS; Thornton, JG
Abstract : Objective: Induction of labour at 39 weeks for nulliparous women aged 35 years and over may prevent stillbirths and does not increase caesarean births, so it may be popular. But the overall costs and benefits of such a policy have not been compared. Design: A cost–utility analysis alongside a randomised controlled trial (the 35/39 trial). Setting: Obstetric departments of 38 UK National Health Service hospitals and one UK primary‐care trust. Population: Nulliparous women aged 35 years or over on their expected due date, with a singleton live fetus in a cephalic presentation. Methods: Costs were estimated from the National Health Service and Personal Social Services perspective and quality‐adjusted life‐years (QALYs) were calculated based on patient responses to the EQ‐5D at baseline and 4 weeks. Main outcome measures: Data on antenatal care, mode of delivery, analgesia in labour, method of induction, EQ‐5D (baseline and 4 weeks postnatal) and participant‐administered postnatal health resource use data were collected. Results: The intervention was associated with a mean cost saving of £263 and a small additional gain in QALYs (though this was not statistically significant), even without considering any possible QALY gains from stillbirth prevention. Conclusion: A policy of induction of labour at 39 weeks for women of advanced maternal age would save money. Tweetable abstract: A policy of induction of labour at 39 weeks of gestation for women of advanced maternal age would save money. Tweetable abstract: A policy of induction of labour at 39 weeks of gestation for women of advanced maternal age would save money.